Kompetensi Pedagogik Guru dalam Penyusunan Rencana Pembelajaran Melalui Supervisi Akademik - Andi Triana (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
The purpose of this research is to describe whether 1) Teachers have never participated in RPP preparation training so they only copy and paste with their friends, even though often the copied and pasted RPP is not relevant to the situation and conditions in their school so that the existing RPP cannot be used as a reference in the learning process . 2). Teachers have attended training, but have not been able to implement it in schools. Research has been carried out at MIN 3 FLAT LAND for the 2019-2020 academic year. This research was carried out on 12, 19, 26 September 2019. This School Action Research was carried out in 2 cycles. Each cycle 1 includes 2 meetings, while cycle 2 is 1 meeting. The data used in this study is qualitative data. Qualitative data is taken from observations, questions and answers, questionnaires, and product results. The data has been analyzed using the Constant Comparative Method. The findings from research on the preparation of learning implementation plans through the academic supervision of school principals can be concluded that:In the component for the formulation of learning objectives indicators, there was an increase from 40% in the initial ability to 60% in cycle 1 and increased to 70% at the end of the activity.In the Components of Determining materials and learning materials, there is an increase in ability from 65% to 70% after cycle 1 and further strengthened to 80%. In the Component Selection of Learning Strategies and Methods, which includes learning steps and determining the allocation of time used, there is a significant increase from the initial 40% to 60% in cycle 1 and increases again to 75% after cycle 2. Although there is no visible increase that is quite sharp, in the component of selecting media and learning tools there is also an increase from 60% at the beginning of the activity and after cycle 1, to 80% after cycle 2. We can also see a significant increase in the planning evaluation component of learning . From the initial 40% at the beginning of the activity, it became 60% at the end of cycle 1 and managed to reach 70% at the end of cycle 2. Looking at the data obtained from research results in this school action research activity, it can be concluded that the academic supervision carried out by the principal of the school The 5 teachers who did not have a teacher education background managed to improve their pedagogical competence in preparing lesson plans.